Improved Environmental DNA Reference Library Detects Overlooked Marine Fishes in New Jersey, United States - Stoeckle, Mark Y.; Das Mishu, Mithun; Charlop-Powers, Zachary (Frontiers in Marine Science, 2020)
An accurate, comprehensive reference sequence library maximizes information gained from environmental DNA (eDNA) metabarcoding of marine fishes. Here, we used a regional checklist and early results from an ongoing eDNA time series to target mid-Atlantic U.S. coastal fishes lacking reference sequences. We obtained 60 specimens representing 31 species from NOAA trawl surveys and institutional collections, and analyzed 12S and COI barcode regions, the latter to confirm specimen identification. Combined with existing GenBank accessions, the enhanced 12S dataset covered most (74%) of 341 fishes on New Jersey State checklist including 95% of those categorized abundant or common. For eDNA time series, we collected water samples approximately twice monthly for 24 months at an ocean and a bay site in New Jersey. Metabarcoding was performed using separate 12S primer sets targeting bony and cartilaginous fishes. Bioinformatic analysis of Illumina MiSeq fastq files with the augmented library yielded exact matches for 90% of the 104 fish amplicon sequence variants generated from field samples. Newly obtained reference sequences revealed two southern U.S. species as relatively common warm season migrants: Gulf kingfish (Menticirrhus littoralis) and Brazilian cownose ray (Rhinoptera brasiliensis). A beach wrack specimen corroborated the local presence of Brazilian cownose ray. Our results highlight the value of strengthening reference libraries and demonstrate that eDNA can help detect range shifts including those of species overlooked by traditional surveys.